2009
DOI: 10.1523/jneurosci.1067-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by the NR3A Subunit of the NMDA Receptor

Abstract: Hyperactivation of NMDA-type glutamate receptors (NMDARs) results in excitotoxicity, contributing to damage in stroke and neurodegenerative disorders. NMDARs are generally comprised of NR1/NR2 subunits but may contain modulatory NR3 subunits. Inclusion of NR3 subunits reduces the amplitude and dramatically decreases the Ca 2ϩ permeability of NMDAR-associated channels in heterologous expression systems and in transgenic mice. Since excessive Ca 2ϩ influx into neurons is a crucial step for excitotoxicity, we ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 30 publications
2
76
0
2
Order By: Relevance
“…There are two major subtypes of NMDAR including the functional subtype NMDAR1, and the regulatory subtype NMDAR2. Studies have found that NMDAR can regulate the synaptic growth, development and plasticity through changing the ratio of NMDAR1/NMDAR2, NO-mediated enzyme and the ion channel [15,16], and ultimately regulate signal transmission between synapses. Therefore, studies on NMDAR1 expression might provide insights into the role of NMDAR1 in the pathogenesis of AD.…”
Section: Discussionmentioning
confidence: 99%
“…There are two major subtypes of NMDAR including the functional subtype NMDAR1, and the regulatory subtype NMDAR2. Studies have found that NMDAR can regulate the synaptic growth, development and plasticity through changing the ratio of NMDAR1/NMDAR2, NO-mediated enzyme and the ion channel [15,16], and ultimately regulate signal transmission between synapses. Therefore, studies on NMDAR1 expression might provide insights into the role of NMDAR1 in the pathogenesis of AD.…”
Section: Discussionmentioning
confidence: 99%
“…GluN3A is expressed primarily in early postnatal life, whereas GluN3B is found in adult brainstem and spinal cord (Petralia and Wenthold, 2008). GluN3A expression seems to be a critical step in synaptogenesis and spine formation, and it maintains receptors in an immature state (Pérez-Otañ o et al, 2006), perhaps with enhanced neuroprotection (Nakanishi et al, 2009). Subsequent down-regulation of GluN3A expression is important for synapse maturation and the emergence of a competent state for synaptic plasticity (Roberts et al, 2009).…”
Section: Synaptic and Extrasynaptic N-methyl-d-aspartate Receptorsmentioning
confidence: 99%
“…Traditional NMDA receptors are key players in glutamate-facilitated neurotransmission ( 24 ). Studies have suggested that expression of Grin3a is highest in selected regions of the brain in the postnatal period and in the adult retina, where the GRIN3A/NR3A subunit is thought to inhibit NMDA receptor Ca 2+ permeability and has a neuroprotective function ( 25 ). Similarly, expression of Grin3a is high in the neonatal kidney, but expression does persist into adulthood.…”
Section: Cluster Of Qtl On Distal Chr 19 Can Be Narrowed To a Small Nmentioning
confidence: 99%